Pengaruh Karakteristik Marketing Syariah terhadap Keputusan menjadi Nasabah BMT UGT Sidogiri Cabang Pamekasan - Khafiatul Hasanah (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2016)
Islamic financial institutions continue to plague the urban to the rural. No exception to the Baitul Maal Wat Tamwil (BMT) in Pamekasan area. Consequently, all the processes required to implement management based on Islamic principles, as well as in marketing. That is why ethics and morals become a necessity in carrying out any business activity. BMT UGT Sidogiri Pamekasan branch is one of the BMT which has increased exponentially customers. Allegedly due to the increase in the number of customers continued to increase customer confidence. One of the flagship products owned BMT UGT Sidogiri Pamekasan branch in collecting funds is Islamic savings have minimum deposit Rp 1000 by the facility pick up the ball that is not offered by other BMT in Pamekasan. Based on this background, researchers interested in conducting research with the title "Influence of Characteristics Marketing Decision Against Sharia Become Customer BMT UGT Sidogiri Pamekasan branch". The problem that arises is there any influence of sharia marketing characteristics to the decision as a customer and what variables (theist, ethical, realistic, humanistic) the dominant influence on a customer's decision. This type of research is field research using a quantitative approach. The study population were all customers of BMT UGT Sidogiri Pamekasan branch using simple random sampling method and the determination of the number of samples is determined by the formula slovin at an error rate of 10%. Mechanical analysis is multiple regression analysis. Simultaneous calculation results obtained Fhitung (39.081)> Ftabel of (2.47) which means accepting the hypothesis of the influence of sharia marketing characteristics (theist, ethical, realistic, humanistic) against the decision of a customer. While the partial test results obtained for thitung theistic, ethical, realistic and humanistic respectively 2.648, 3.622, 2.560, 2.938 greater than ttable (1.66123), which means either partially theistic, realistic, realistic and humanistic declared significant. So that the ethical is the most dominant variable influence on a customer's decision BMT UGT Sidogiri Pamekasan branch.